(4R*,4aS*,4bS*,5R*,10aR*)-4-Hydroxy-4a,5-dimethyl-2-(propan-2- yl)-1,4,4a,4b,5,6,7,8,10,10a-decahydrophenanthren-1-one - Caracelli, I.; Zukerman-Schpector, J.; Lousada Machado, A.T.; Brocksom, T.J.; Lucia Ferreira, M.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
In the title compound, C(19)H(28)O(2), the A ring adopts a chair conformation. Both the B and C rings adopt envelope conformations with the C atoms common to both rings and adjacent to the carbonyl and hydroxyl groups, respectively, lying 0.604 (3) and 0.634 (3) angstrom out of the mean planes defined by the remaining five C atoms of rings B and C, respectively (r.m.s. deviations = 0.0100 and 0.0157 angstrom, respectively). The formation of linear supramolecular C(7) chains along the a axis mediated by hydroxy-O-H center dot center dot center dot O(carbonyl) hydrogen bonds is the most prominent feature of the crystal packing.